Routledge handbook of energy law - Hunter, Tina Soliman (London : Routledge, 2020)
The Routledge Handbook of Energy Law provides a definitive global survey of the discipline of Energy Law, capturing the essential and relevant issues in Energy today. Each chapter is written by a leading expert, and provides a contemporary overview of a significant area within the field. The book is divided into six geographical regions based on continents, with a separate section on Russia, an energy powerhouse that straddles both Europe and Asia. Each section contains highly topical chapters from authors who address a number of core themes in Energy Law and Regulation: Energy security and the role of markets Regulating the growth of renewable energy Regulating shifts in traditional forms of energy Instruments in regulating disputes in energy Impact of energy on the environment Key issues in the future of energy and regulation. Offering an analysis of the full spectrum of current issues in Energy Law, the Routledge Handbook of Energy Law is an essential resource for advanced students, researchers, academics, legal practitioners and industry experts.
OCLC-licensed vendor bibliographic record.
Keywords: Energy industries -- Law and legislation; Energy development -- Law and legislation; LAW / General; LAW / International